Implementasi Manajemen Partisipatif dalam Pengembangan Budaya Religius di Sekolah - Mambaul Ngadhimah (Proceedings of Annual Conference for Muslim Scholars, 2017)
Religious culture is built on moral values and religion to be applied in the behavior and organizational culture in the school. Religious culture will be solid if the whole school community involved in the decision making process. The research focuses on the study of: Implementation of Participatory Management in the Development of Religious Culture in SMAN I Kwadungan Ngawi on: (1) The development of religious culture in schools; (2) Implementation of participatory management by the school community in the development of religious culture; (3) The response of the school community in a participatory management process in the development of religious culture. This study developed the theory of management is participatory, with theoretical contributions that we call the theory of pre-management ourselves where the participation of the school community can be implemented properly if stakeholders are willing and able to communicate to cooperate with all the elements in carrying out the structure, functions and responsibilities, to optimize processes, the implementation and results of the program that has been agreed upon.Keywords: Participatory Management, Values, Response, Religious Culture